Regenerative medicine: targeted genome editing in vivo - Wang, Lixia (Cell Res, 2015)
The CRISPR/Cas system has proven to be a powerful gene editing tool both in vitro and in vivo. A recent flurry of studies of in vivo gene editing using the CRISPR/Cas system bring bright prospects in creating animal models and targeted gene therapy of human genetic diseases.